Why Is Needed the Radical Change of the Newly Legislation of Development of the Bulgarian Academic Staff [In Bulgarian] - I. Drenovski (University of Sofia, 2019)
The article sets out arguments for potentially unconstitutional new texts of the Act of the Academic Staff Development from year 2018 and discriminatory provisions of its Implementing Rules. Some discrepancies between the Act and the National Classification of Occupations and Positions, as well as contradic-tory provisions of the Regulation on the Establishment of the Academic Staff Register, are being discussed.